2008
DOI: 10.1634/stemcells.2007-0877
|View full text |Cite
|
Sign up to set email alerts
|

Androgenetic Embryonic Stem Cells Form Neural Progenitor Cells In Vivo and In Vitro

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
12
2
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 49 publications
5
12
2
2
Order By: Relevance
“…Although uniparental embryos are not capable of full-term development due to defects in genomic imprinting, androgenetic ESCs and gPS cells can generate normal chimeras. 5,14 Using blastocyst injection of androgenetic ESCs, Dinger et al demonstrated their contribution to the development of chimeric fetal brains. This suggests that proper expression of imprinted genes, such as Ndn, which has a role in neurogenesis, is associated with a transition from the androgenetic imprinting pattern to somatic-like patterns during reprogramming of SSCs into gPS cells.…”
Section: Derivation Of Nscs From Gps Cellsmentioning
confidence: 99%
“…Although uniparental embryos are not capable of full-term development due to defects in genomic imprinting, androgenetic ESCs and gPS cells can generate normal chimeras. 5,14 Using blastocyst injection of androgenetic ESCs, Dinger et al demonstrated their contribution to the development of chimeric fetal brains. This suggests that proper expression of imprinted genes, such as Ndn, which has a role in neurogenesis, is associated with a transition from the androgenetic imprinting pattern to somatic-like patterns during reprogramming of SSCs into gPS cells.…”
Section: Derivation Of Nscs From Gps Cellsmentioning
confidence: 99%
“…Eckardt et al demonstrated that mouse AgESC-derived hematopoietic stem cells in the fetal liver convey long-term and multilineage reconstitution of the entire hematopoietic system in the recipient without any associated pathologies [11]. Furthermore, Dinger et al observed the widespread contribution of AgESCs in fetal chimeric mice and reported that their neural differentiation potentials or self-renewal properties of neural stem cells did not differ from normal biparental ESCs [14]. Therefore, it seems that the characteristic phenotypes of AgESCs, such as status of genomic imprinting, might not be seriously problematic in adult animals or in the in vitro differentiation process, and the potential of AgESCs as transplants in many kinds of disorders might be worth considering.…”
mentioning
confidence: 99%
“…Dieses unterschiedliche Besiedlungsmuster wird auf AG-beziehungsweise PG-spezifische imprinted Genexpression im Gehirn zurückgeführt. In differenzierenden AG-ES-Zellen zeigte sich, dass diese Zellen trotz eines fehlenden mütterlichen Genoms neurale Stammzellen (AG-NSCs) bilden, die sich in ihrer Fähigkeit zur Selbsterneuerung und im Multilinien-Differenzierungspotenzial nicht von normalen neuralen Stammzellen (NSCs) unterscheiden (Dinger et al, 2008). Ferner können AG-ES-Zellen zu dopaminergen Neuronen 25 differenzieren (Choi et al, 2005), die neuronale Aktionspotenziale generieren (Wolber, 2013).…”
Section: Mesenchymale Stamm-/stromazellen (Mscs)unclassified
“…Ferner können AG-ES-Zellen zu dopaminergen Neuronen 25 differenzieren (Choi et al, 2005), die neuronale Aktionspotenziale generieren (Wolber, 2013). Dabei bleibt die rein väterliche Genexpression erhalten (Dinger et al, 2008).…”
Section: Mesenchymale Stamm-/stromazellen (Mscs)unclassified